PASD1 Expression in Malaysian Hematological Malignancies Patients (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
Per ARNT SIM domain containing 1 (PASD1) protein belongs to the Cancer Testis Antigen (CTA) family. It shows restricted expression in normal tissues but are highly expressed in cancer tissues. This study aims to further investigate PASD1 expression in Malaysian hematological malignancies patients as a potential biomarker for disease progression and vaccine development. Formalin-fixed Paraffin-Embedded (FFPE) tissue specimens from hematological malignancies patients were labeled with anti-PASD1-1 and anti-PASD1-2 antibodies using immunohistochemistry method. Our results show that among DLBCL patients, 7 samples were positive for PASD1-1, 2 samples were positive for PASD1-2 while 3 samples were positive for both of the antibodies. In addition, only 1 sample from T-cell Lymphoblastic Lymphoma (TLL) showed positive staining with PASD1-1. Other classes of hematological malignancies did not show any positive staining with either antibody. Antibody PASD1-1 stained the membrane and cytoplasm of the tumor cells strongly. Moderate nuclear labeling was also observed in some cases of DLBCL with PASD1-2. PASD1-1 staining was more frequent compared to PASD1-2 in most of the samples. Positive PASD1 staining was observed in patients with age range between 36-71 years old, higher in male cases than female by 54% and higher in Malay patients compared to Chinese by 77%.  Due to its frequency, the PASD1_v1 protein may play a role in the DLBCL initiation and progression. A higher number of PASD1 staining in DLBCL samples compared to other lymphoma subtypes may suggest that PASD1 may represent a potential for DLBCL subtyping marker.
Keywords: Lymphoma; PASD1; Expression; Antibody; DLBCL